Modelirovaniye trenirovochnykh zadanii v sportivnoi bor'be - Podlivaev, B. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The problems of the training tasks` modelling are considered in the article in connection with wrestlers sporting mastery`s improvement. The author offers to use the classification of the wrestling`s elements of technique and tactics as well as the results of the analyses competitive activities, the individual peculiarities in fighting conducting of elite wrestlers, and subjective factors of refereeing as the basis for formal (situational) modelling.